Effects of Speech Intensity on the Callsign Acquisition Test (CAT) and Modified Rhyme Test (MRT) Presented in Noise - BLUE-TERRY, Misty; McBRIDE, Maranda; LETOWSKI, Tomasz (Archives of Acoustics, 2013)
This study sought to evaluate the effect of speech intensity on performance of the Callsign AcquisitionTest (CAT) and Modified Rhyme Test (MRT) presented in noise. Fourteen normally hearing listenersperformed both tests in 65 dB A white background noise. Speech intensity varied while background noiseremained constant to form speech-to-noise ratios (SNRs) of −18, −15, −12, −9, and −6 dB. Resultsshowed that CAT recognition scores were significantly higher than MRT scores at the same SNRs; how-ever, the scores from both tests were highly correlated and their relationship for the SNRs tested can beexpressed by a simple linear function. The concept of CAT can be easily ported to other languages fortesting speech communication under adverse listening conditions.